Cognitive disorders problem in the context of depressive symptoms in patients with post-traumatic stress disorder - Napryeyenko , Олександр; Napryeyenko , Наталія; Dolynskyi, Роман (Psychosomatic Medicine and General Practice, 2021)
This text is the conference abstract to the materials of the poster report to the IV scientific-practical conference with international participation "Psychosomatic medicine: science and practice". It is dedicated to cognitive disorders problem of in the context of depressive symptoms in patients with Post-traumatic stress disorder.